Fish Health Management Considerations in Recirculating Aquaculture systems - Part 3: General Recommendations and Problem-Solving Approaches - Roy Yanong (EDIS)
Both the popularity and use of recirculating systems have increased, and these systems are now commonly used in aquaculture facilities, wholesale and retail tropical fish facilities, and public aquaria. This circular is Part 3 of a three-part series dealing with fish health management in recirculating aquaculture systems. This document provides general recommendations for choosing, setting up, and running a system, as well as some problem-solving approaches to help maintain a well-managed system – regardless of its purpose. This basic information should assist the beginner or intermediate-level aquaculturist interested in maintaining healthy fish in recirculating systems. This document is Circular 122, one of a series from the Department of Fisheries and Aquatic Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2003.